MAIN EPIDEMIOLOGICAL ASPECTS OF PANCREATIC CANCER IN KAZAKHSTAN - Fazyl , F.; Begimbetova , D; Batyrbekov , K.; Spataev , Z.; Aitbaev , Sh.; Sarbassov , D. (Eurasian Journal of Applied Biotechnology, 2022)
According to GLOBOCAN (2020), pancreatic cancer (PC) is in 12th place among oncopathology in terms of incidence - 4.9 cases per 100,000 population. Most cases of pancreatic cancer are registered in China, the USA, Japan, and Germany. In the structure of mortality among oncological diseases, pancreatic cancer occupies 9th place - 4.5 cases per 100 thousand of the population. According to epidemiological studies, by 2040, a 79.9% increase in mortality from pancreatic cancer is predicted. According to statistics, in the United States, there is an increase in the incidence of cancer in the distal pancreas. In addition, early stages of pancreatic cancer were diagnosed more often and less often - the 4th. One of the trends in the epidemiology of pancreatic cancer is an increase in the incidence of this pathology among young people. Factors contributing to the development of pancreatic cancer in people under 50 years of age are genetic mutations, smoking, and obesity. A retrospective statistical analysis of the epidemiological state of pancreatic cancer in Kazakhstan over 3 years was carried out (standardized WHO World indicators per 100,000 population and intensive indicators of morbidity, mortality, distribution by stage, age, and sex), and regional features of pancreatic cancer were studied.